Evidence producing organizations: Organizational translation of travelling evaluation ideas. (July 2019) - Elvbakken, Kari Tove; Hansen, Hanne Foss
In the 1990s and 2000s, the evidence wave in evaluation practice gained momentum first in medicine later in other policy fields. The evidence idea inspired actors in Scandinavia where evidence producing organizations were established. The aim of our study is to better understand these organizations and explore their characteristics in Denmark and Norway. We compare their organizational structures, stance towards ministries, resources and governance frameworks and analyse organizational change across time. Although the ideas of evidence-based policy and practice are common in the two countries, the organizations and context for evidence producing activities differ. Furthermore, in policy fields outside medicine the evidence movement is struggling to maintain support and resources.